Le moment anthropologique du cinéma industriel pharmaceutique. Retour sur le film utilitaire médico-pharmaceutique francophone des années 1970 - Christian Bonah; Joël Danet (Images du Travail, Travail des Images)
The contribution investigates a series of industrials films produced in the pharmaceutical sector in the 1970s. Their particularity lies in the fact that beyond their context of commission the films bear evident witness to anthropological documentary film of the same period. Addressing the specific audience of physicians, the films invest the study of psychological patterns of physician-patient interaction conceived as a structural element of care giving. Produced by a series of pharmaceutical industries the films subscribe to communication strategies of industrial players for medical professionals. Nevertheless their filmic approach seems at first hand rather incompatible with the logic of promotion: a sober mise-en-scène, little artefacts, often long and even tedious sequences with dialogues caught in real action and overall strongly related to cinema-direct. The text inquires how rationales of communication could be and were linked to an anthropological approach in these moving images, what their hybridization implies as to forms legitimizing medical knowledge and which pharmaceutical interests lay beneath these surprising and hybrid utility films.